Association of kisspeptin-10 levels with abortus imminens: a preliminary study - Kavvasoglu, Serif; Ozkan, Zehra Sema; Kumbak, Banu; Simsek, Mehmet; Ilhan, Necip (Springer Heidelberg, 2012)
To investigate the association between kisspeptin 10 (Kp-10) levels and early pregnancy bleeding and perinatal outcome. A total of 20 pregnant women with the complaint of vaginal bleeding during 7-18 gestational weeks and 20 healthy gestational week matched pregnant women were included in the study. Maternal plasma Kp-10 levels were measured with the enzyme immunoassay method. Adverse pregnancy outcomes like intrauterine growth restriction, preterm delivery, preeclampsia and low birth weight were evaluated in both groups. Maternal plasma Kp-10 levels (p = 0.01) and birth weight (p = 0.06) were found to be lower in women with bleeding. Intrauterine growth restriction, preterm delivery and intrauterine exitus were noted more commonly in women with bleeding (10 vs. 0%, 25 vs. 15% and 20 vs. 0%, p = 0.08). Preeclampsia were developed in 5% of both groups. Kp-10 levels showed positive correlation with gestational week (p = 0.02) and ALT levels (p = 0.02). Kp-10 levels were found lower in women with early pregnancy bleeding.
Keywords: Early pregnancy bleeding; Kisspeptin-10; Pregnancy outcome; Trophoblast invasion